A novel DOPA-albumin based tissue adhesive for internal medical applications. (December 2017) - Zhu, Wenzhen; Peck, Yvonne; Iqbal, Jabed; Wang, Dong-An
Abstract: To date, existing tissue adhesives have various weak points in gluing kinetics and stability – particularly, in biocompatibility, which make most of them remain suboptimal for internal conditions. Herein, a novel mussel-inspired "BCD" tissue glue made of bovine serum albumin (BSA), citrate acid (CA) and dopamine was developed aiming at internal medical applications. BSA was employed as a natural and biocompatible macromolecular backbone; CA was introduced as a dual-functional intermediate to increase reactive carboxyl sites for engraftment of dopamine onto BSA backbone and also block the competing reactive amines from the proteinic backbone. Timely curing and stable adhesion were achieved between biological tissue substrates via instant chelation and gradual conjugation of DOPA-catechol groups in BCD glue. Within 30 min, this newly developed BCD tissue glue can provide over 10-fold greater adhesion stress than that of commercially available fibrin glue in wet environment. As a tissue adhesive for internal use, its superior properties also include ideal gelation kinetics and swelling behaviour, appropriate degradation rate, sound cytocompatibility in vitro, as well as fine biocompatibility in vivo. More importantly, successful animal experimentations in seroma prevention and instant hemostasis ultimately validated BCD tissue glue's preclinical efficacy as a tissue adhesive for various internal medical applications.